Aquatic Learning Approach for Improving Early Childhood Basic Attitude - Hafina, Anne; Nur, Lutfi; Rusmana, Nandang (Universitas Pendidikan Indonesia, 2019)
This study was conducted to determine the contribution of the aquatic learning approach to the development of the basic attitude ability in early childhood. This study used one group pretest-posttest design with 8 students aged 5-6 years as participants. The instruments used in this study were structured observations and field notes reflecting the children’ basic attitudes, including respecting rules, sharing equipment, fearless, listening to instructions, and the desire to participate. The data analysis technique used was paired sample t-test. The results showed that the children basic attitude ability increased significantly with t-value 7.514. However, the research with a larger number of participants is needed to find out the impact in general. AbstrakPenelitian ini dilakukan untuk mengetahui kontribusi pendekatan pembelajaran aquatik terhadap pengembangan kemampuan sikap dasar anak usia dini. Penelitian ini menggunakan one group pretest-posttest design dengan subyek penelitian adalah siswa taman kanak-kanak berusia 5-6 tahun sebanyak 8 siswa. Instrumen dalam penelitian ini menggunakan observasi terstruktur dan catatan lapangan mengenai sikap dasar anak yang meliputi menghormati aturan, berbagi perlengkapan, tanpa rasa takut, mendengarkan intruksi dan keinginan untuk berpartisipasi. Teknik analisis data yang digunakan adalah paired sample t-test. Hasil penelitian menunjukkan bahwa kemampuan sikap dasar anak usia dini mengalami peningkatan yang signifikan dengan nilai t sebesar 7,514. Penelitian dengan jumlah partisipan yang lebih besar perlu dilakukan untuk mengetahui dampaknya secara umum.